Türkiye de ki Üniversitelerde Sağlık Yönetimi Eğitiminde Muhasebe ve Finansman Dersleri Durum Analizi - Şahin, Sibel (Turk Turizm Arastirmalari Dergisi, 2020)
The increase in competition and costs in the health sector has revealed the need for managers to ensure the advancement of technology and more efficient and efficient use of resources. For this purpose, associate degree in health administration in Turkey, undergraduate and postgraduate education is given. It is seen that accounting and finance courses are also included in thesetrainings. In the field of health management, this study was carried out in order to determine the accounting and finance courses in associate, undergraduate, graduate and doctorate programs, the elective or compulsory courses of these courses and in which semester they are taught. As a result of the research, although it has the same contents, it is seen that there are courses withdifferent names. Also, it was determined that the General Accounting course is included in the associate and undergraduate curriculum of almost all universities and is compulsoryly taught, while the Financial Management course in Healthcare Institutions is a compulsory course in undergraduate programs, although it is included as an elective course in some of the associate degree programs. In master's programs, it is seen that cost accounting and financial management courses are generally elective or compulsory.
Keywords: 4. Education